2017
DOI: 10.1248/cpb.c16-00767
|View full text |Cite
|
Sign up to set email alerts
|

Iron(II)porphyrin–Cyclodextrin Supramolecular Complex as a Carbon Monoxide-Depleting Agent in Living Organisms

Abstract: The specific intermolecular interaction between an anionic tetraarylporphyrin and per-O-methylated β-cyclodextrin (TMe-β-CD) paved the way to produce a functional supramolecule that works as a strong carbon monoxide (CO)-depleting agent in living organisms. The supramolecular complex, hemoCD, that is composed of meso-tetrakis(4-sulfonatophenyl)porphinatoiron(II) and a TMe-β-CD dimer linked by a pyridine linker, captured internal CO from carboxyhemoglobin during its circulation in the blood of animals. HemoCD t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Our data show that the CO-hemoCD1 complex, unlike CO-Hb, is extremely stable and hardly decomposes under extreme conditions such as high pressures of N 2 and O 2 , or in the presence of oxidants (H 2 O 2 ). The facts that hemoCD1: (1) is not cell-permeable 39 and not easily denatured by other chemicals; (2) can be isolated from other biocomponents; and that (3) its O 2 binding affinity is moderate (Table 2 ) enabling CO to easily replace O 2 , make it a unique molecule with suitable properties as a CO scavenging agent in the biological environment. Another important property is that hemoCD1 also exhibits a much higher CO binding affinity compared to NO and H 2 S.…”
Section: Discussionmentioning
confidence: 99%
“…Our data show that the CO-hemoCD1 complex, unlike CO-Hb, is extremely stable and hardly decomposes under extreme conditions such as high pressures of N 2 and O 2 , or in the presence of oxidants (H 2 O 2 ). The facts that hemoCD1: (1) is not cell-permeable 39 and not easily denatured by other chemicals; (2) can be isolated from other biocomponents; and that (3) its O 2 binding affinity is moderate (Table 2 ) enabling CO to easily replace O 2 , make it a unique molecule with suitable properties as a CO scavenging agent in the biological environment. Another important property is that hemoCD1 also exhibits a much higher CO binding affinity compared to NO and H 2 S.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, the CO binding affinity of hemoCD1 is the highest among the reported native CO-binding proteins. The administration of hemoCD1 to animals (rats and mice) did not show any significant side effect except for endogenous CO scavenging (35)(36)(37)(38). Most of the administered hemoCD1 is excreted in the urine as CO-hemoCD1 complex within one hour.…”
Section: Introductionmentioning
confidence: 96%
“…The biomedical applications of the supramolecular Por/CD Me system have been demonstrated by us and other research groups and reviewed in recent papers. [13][14][15][16][17] We recently investigated selective detection with the Por/CD Me complex in biological media, including serum, blood, and urine, using 5,10,15,20-tetrakis(4-sulfonatophenyl) porphyrin (TPPS) and 13 C-labeled heptakis(2,3,6-tri-O-methyl-13 C)-β-cyclodextrin ( 13 C-CD Me ). [18] Several NMR techniques revealed that the supramolecular 1 : 2 TPPS/ 13 C-CD Me complex is quite stable and detectable in these biologically crowded media, that contain many biocomponents, including proteins and lipids.…”
Section: Introductionmentioning
confidence: 99%